Exploring the Nuances of Nurse-Patient Interaction through Concept Analysis: Impact on Patient Satisfaction. (January 2016) - Evans, Emily C.
Patient satisfaction is a major priority in healthcare. Nurse-patient interaction has a direct effect on patient satisfaction and is essential to the provision of nursing care. Using the Avant and Walker method of concept analysis, the author explores what shapes nurse-patient interaction; the defining attributes, antecedents, consequences and empirical referents. In addition, cases are provided that illustrate various types of nurse-patient interaction. The author also discusses the concept of nurse-patient interaction in light of current nursing research trends and priorities, adding to the base of nursing knowledge that will facilitate the highest quality nursing care and patient satisfaction.